A Comprehensive Literature Review of Osteoporosis Treatment and Fracture Outcomes - Indra Hadi Rapmartua Ompusunggu; Immanuel (International Medical Journal Corp. Ltd, 2024)
Background: Osteoporosis remains a significant public health concern, particularly among the aging population, where the prevalence of the condition and associated fractures continues to rise. The literature surrounding osteoporosis treatment and fracture outcomes has evolved considerably over the past decade, reflecting advancements in pharmacotherapy and the importance of patient-centered care. Literature Review: The foundational article by (Body et al., 2012) highlights the expanding pharmacological options available for osteoporosis management, stressing the complexities involved in treatment selection due to the limited comparative evidence. This article sets the stage for understanding the broader landscape of osteoporosis therapies, where both skeletal and extraskeletal effects of treatments must be considered for informed clinical decision-making. In examining the treatment landscape, (Fontalis et al., 2019) provides insights into the mechanisms of action of various agents, such as bisphosphonates and denosumab, and discusses emerging therapies that may enhance treatment efficacy. This article underscores the importance of understanding the long-term safety profiles of these medications, as adverse effects can significantly influence treatment outcomes. Moreover, (Lin et al., 2021) offers a comprehensive meta-analysis comparing the efficacy and safety of various osteoporosis treatments for postmenopausal women. This work is pivotal in guiding clinicians toward selecting appropriate interventions based on the relative effectiveness of available therapies, particularly in the context of fracture prevention. Conclusion: In conclusion, the literature collectively emphasizes a comprehensive approach to osteoporosis management that incorporates advancements in pharmacotherapy, addresses adherence challenges, and prioritizes patient-centered care. This multifaceted strategy is critical for optimizing fracture prevention and improving the overall quality of life for individuals with osteoporosis.